Comparison between Absolute and Relative Quantification of LINE-1 Methylation Level in Breast Cancer - Than, Nguyen Thi; Trang, Tran Thi Quynh; Phuong, Luu Thi Thu; Oanh, Pham Minh; Hoa, Vu Mai; Tung, Pham The; Linh, Vuong Dieu; Quang, Nguyen Ngoc; Lan, Vo Thi Thuong (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 2, 2026)
There are two accurate formulas corresponding to absolute and relative methods that were widely used for quantitative DNA methylation level. In the absolute method, DNA methylation is examined by two sets of MSP primers, one is specific for the methylated state and the other for the unmethylated state of the target. In the relative method, DNA methylation is examined by two sets of primers, one is MSP, specific for the methylated state, and the other is MIP, for the measurement of input DNA levels to normalize the signal for each methylation reaction. Both these methods, subjected to quantitative measurement of the LINE-1 methylation level in breast cancer samples, indicating LINE-1 hypermethylation in tumour tissue samples as compared with adjacent tissue samples. The methylated LINE-1 amount is enormous but the unmethylated one is scant, consequently leading to greater measurement variance compared with the comparative quantification.Thus, the relative quantification, may be a more convenient method for quantitatively measuring the LINE-1 methylation level.